Analisis Pendapatan Usahatani Sawi Sendok (Brassica Chinensis L.) “Pakcoy” Di Kelurahan Rurukan Kecamatan Tomohon Timur - Mongdong, Deanita Regina; Pangemanan, Lyndon Reinhard Jacob; Memah, Melsje Yellie (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the income of mustard greens farming "pakcoy" in Rurukan Village, East Tomohon District. This research was conducted for 2 months, from August to October 2022. The data analysis method used in this study was descriptive analysis. The data used are primary data and secondary data. The primary data was obtained by means of a survey through the face-to-face stage using a questionnaire which contained a list of questions regarding the identity of the respondent, the input and output of the "pakcoy" mustard spoon farming. Secondary data obtained from books or literature related to the problem under study. The results showed that the total production of mustard spoon "pakcoy" obtained in one harvest of mustard spoon "pakcoy" was 759.09 Kg with a cultivated area of 0.162 Ha. The price that applies to farmers is IDR21,818/10Kg. The total costs incurred by farmers in one harvest of the mustard spoon "pakcoy" average IDR609,741. The total income of the "pakcoy" spoon mustard farmers in this business averages IDR1,381,818. The total income of mustard greens farmers with an average "pakcoy" spoon is IDR772,077 and the results of the R/C ratio analysis in one harvest show that the "pakcoy" spoon mustard farming is profitable for farmers so that it can be continued and developed.